Long-term change of the eruption activities of Sakurajima volcano, Japan, inferred from the fallout tephra deposits - Nishihara, Ayumu; Geshi, Nobuo; Naruo, Hideto (Frontiers in Earth Science, 2022)
Stratigraphic analysis of fallout tephra deposits in and around a volcano provides a framework for understanding the long-term temporal change in the volcano’s activities. Here, we reconstruct the evolution of the volcanic activities of Sakurajima volcano based on reconstructed tephra stratigraphy by original field surveys, compilations of geological and archeological data, and new 14C dating. We define three eruption stages of Stage 1 (30–24 ka), Stage 2 (12.8–4.8 ka), and Stage 3 (4.5 ka–present), based on a major hiatus and shifting of the volcanic centers. Stages 2 and 3 are further subdivided according to the predominant mode of volcanic activity. Revised distribution of tephra deposits indicates that a total of 14.5 km3 (5.8 km3 dense rock equivalent) of fallout tephra has erupted from Sakurajima. Among them, Stage 2a (13–8 ka) produced the largest volume of tephra fallout deposits, suggesting that Sakurajima peaked in magma discharge during Stage 2a (2.9 km3/kyr) and then decreased rapidly toward Stage 2b (8–4.8 ka; 0.07 km3/kyr). The eruption of large-volume tephra deposits in Stage 2a, followed by the development of a thick volcanic ash layer in Stage 2b, indicates the eruption style shifted from explosive pumice eruptions in Stage 2a to ash-producing Vulcanian activity in Stage 2b, with decreasing magma discharge rate. Thick volcanic ash deposits covered by several fallout tephra deposits during Stage 3 also reflect a shift in activity from repeated Vulcanian explosions with lava effusions in Stage 3a (4.5–1.6 ka) to predominantly pumice eruptions during the historical period (Stage 3b) with an increasing magma discharge rate. The case study of Sakurajima presented here demonstrates that the combined analysis of the distribution, stratigraphy, and age of pumice fall layers with the lava and pyroclastic cone deposits on the volcanic edifice is a powerful tool for deciphering the growth history of complex stratovolcanoes.